The Role of Islam in the Development of Information and Communication Technology in the Digital Age: A Systematic Literature Review - Dahliana, Dina; Mohamed Mokhtar, Marzni; Peramita, Risna; Maiwinda, Guesa; Mandaria, Vilsa (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
This research aims to explore the contribution of Islam to information and communication technology and the challenges faced in its use. The method used in this research is a qualitative approach with literature analysis, which involves collecting data from various sources, including related articles, books and reports. In the ever-evolving digital age, digital ethics has become an important focus in Islamic teachings, encouraging Muslims to use technology platforms wisely and responsibly. This research found that technological innovations undertaken by Muslims, including the development of applications and devices that support religious practices, have had a positive impact in facilitating worship and deepening the understanding of Islamic teachings. In addition, the accessibility of information offered by information and communication technology allows people to gain knowledge about Islam more widely and easily. However, challenges such as the spread of false information and the digital divide still need to be addressed. Therefore, improving digital literacy and collaborative efforts to improve information and communication technology infrastructure in underserved areas are crucial. It is hoped that this research can provide input for the development of better strategies in utilizing information and communication technology for the benefit of da'wah and Islamic education in the future.